Pendampingan Digital Marketing Pada UMKM Bakso Dan Es Campur “Family” Sebagai Penunjang Kegiatan Promosi Dan Pemasaran - Ainurriyah Ainurriyah; Sugeng Purwanto (Pusat Riset dan Inovasi Nasional, 2023)
Micro, Small and Medium Enterprises (MSMEs) have a very important role in the Indonesian economy. In the era of technological development and digitization in various fields, MSMEs as a type of business that has a large role in building the economy also need to experience development in the field of technology in marketing their products. The purpose of this service is to develop MSMEs in terms of digital marketing and expand the MSMEs marketing network. One example of MSMEs that need digital marketing assistance is UMKM Meatballs and Mixed Ice